KEAHLIAN AKUNTAN FORENSIK DALAM MENGUNGKAP PRAKTIK KORUPSI DI INDONESIA (Studi pada BPK, BPKP, dan KPK) - , PRADHEWA AKBAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of forensic accounting make forensic accountants role in uncovering fraudulent practices in the government agencies more apparent in recent years. Forensic accountants in this case should have basic skills and advanced skills and a strong personality in performing its role as a financial investigator. This study aimed to identify what skills that must be owned forensic accountants to reveal government corruption in Indonesia. This research is a qualitative descriptive survey method. The population used in this study were all forensic accountants Indonesian government, while research samples use sampling technique purposive sampling method which forensic accountants in BPK, BPKP, and KPK. The survey was conducted in November and December 2012. The results of this study indicate that the financial investigation skills are required skills forensic accountants to reveal corruption and attitudes of integrity is that must be owned attitude forensic accountants for uncovering corruption in the government.